Effect of days postburning and calcium oxide on the fermentation, aerobic stability and nutritional characteristics of sugarcane silage for finishing Nellore steers - Roth, Anna Paula T. P. [UNESP]; Siqueira, Gustavo R. [UNESP]; Rabelo, Carlos H. S.; Moretti, Matheus H. [UNESP]; Härter, Carla J. [UNESP]; Resende, Flávio D. [UNESP]; Reis, Ricardo A. [UNESP] (Wiley, 2018)
In this study, the effects of days postburning and calcium oxide (CaO) on the fermentation, aerobic stability and nutritional characteristics of sugarcane silages for finishing Nellore steers were investigated. Silages were prepared in minisilos from in natura and burned sugarcane that remained in the field 1 and 10 days postburning (1-day burned and 10-day burned, respectively). Next, forages were left untreated or treated with CaO (10 g/kg fresh forage). Compared to that in untreated silages, CaO application increased the dry-matter (DM) recovery of in natura, 1-day and 10-day burned silages (p < 0.001) by 67, 179 and 209 g/kg DM respectively. The CaO treatment increased (p < 0.001) the aerobic stability of the in natura and 10-day burned silages by 62.7 and 24.7 hr respectively. In a feedlot experiment, feeding 1-day burned silage reduced DM intake of steers throughout the feedlot period (0–93 days; p < 0.05) compared with that of steers fed in natura silage diet, but the average daily gain (ADG) was lower (p = 0.006) only during the adaptation period (−0.16 kg/day; 0–28 days). The CaO application decreased DM intake (p = 0.007; −1.17 kg/day) and ADG (p < 0.001; −0.13 kg/day) of steers only during the adaptation period likely owing to low silage palatability caused by increased Ca and butyric acid concentrations (≥11.6 g/kg DM). We recommend feeding beef cattle with CaO-treated burned sugarcane silages in low-dietary concentration because of its high butyric acid concentration.
Keywords: aerobic deterioration; alkaline treatment; burned sugarcane; feedlot cattle; lime